Volume 1B: Combustion, Fuels and Emissions 2013
DOI: 10.1115/gt2013-95659
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Nonlinear Dynamics of a Multiple Flame Combustor by Coupling the Describing Function Methodology With a Helmholtz Solver

Abstract: This study focuses on the numerical determination of thermo-acoustic instabilities using a combination of the Flame Describing Function (FDF) methodology and a numerical code solving the Helmholtz equation. In this framework, the FDF is defined by a set of Flame Transfer Functions (FTF) that depend on both the frequency and amplitude of acoustic perturbations. The FDF methodology has been recently used in combination with acoustic network methods to examine the nonlinear stability of generic configurations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…(5) means finding simultaneously the values of σ andp that satisfy Eqn. (5). It should be noted that for a passive flame, where G = 0 and therefore H = 0, and for open (Bp =p) or closed (Bp = ∇p) acoustic boundary conditions, the eigenvalue problem becomes linear in σ .…”
Section: Swirled Combustor Thermoacoustic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…(5) means finding simultaneously the values of σ andp that satisfy Eqn. (5). It should be noted that for a passive flame, where G = 0 and therefore H = 0, and for open (Bp =p) or closed (Bp = ∇p) acoustic boundary conditions, the eigenvalue problem becomes linear in σ .…”
Section: Swirled Combustor Thermoacoustic Modelmentioning
confidence: 99%
“…Appendix A: Using Finite Differences to compute the derivatives of the operator N (σ , η) with respect to σ and η After discretization by finite volumes of the Helmholtz equation (5), the operators A , H and B become square matrices of size N × N, where N is the number of nodes considered. In this study, numerical convergence was reached for N > 6000.…”
Section: Accepted Manuscript N O T C O P Y E D I T E mentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the flame shape had a weak influence at low frequencies due to the small flame scale compared with the acoustic wavelength, while the opposite results were found at high frequencies. Cuquel et al [29] compared the numerical results with experimental ones and those calculated using the low-order model. Both linear and nonlinear unstable modes, as well as the frequency and amplitude, can be obtained using the Helmholtz solver.…”
Section: Introductionmentioning
confidence: 99%